The Emerging Landscape of Long Non-Coding RNAs in Colorectal Cancer Metastasis - Liao, Zhiming; Nie, Hui; Wang, Yutong; Luo, Jingjing; Zhou, Jianhua; Ou, Chunlin (Frontiers in Oncology, 2021)
Colorectal cancer (CRC) is one of the most common gastrointestinal cancers, and it has extremely high rates of morbidity and mortality. The main cause of death in CRC is distant metastasis; it affects patient prognosis and survival and is one of the key challenges in the treatment of CRC. Long non-coding RNAs (lncRNAs) are a group of non-coding RNA molecules more than 200 nucleotides in length. Abnormal lncRNA expression is closely related to the occurrence and progression of many diseases, including cancer. Recent studies have shown that numerous lncRNAs play pivotal roles in the metastasis of CRC, and reversing the expression of these lncRNAs through artificial means can effectively reduce the malignant phenotype of metastatic CRC to some extent. This review summarizes the major mechanisms of lncRNAs in CRC metastasis and proposes lncRNAs as potential targets for clinical treatment of CRC and as molecular markers for early diagnosis.